La obesidad en adolescentes como factor de riesgo de baja capacidad intelectual, medido con el test de matrices progresivas de raven. Instituciones educativas estatales del distrito el porvenir, trujillo 2014 - García Huamán, Lidia Angela (2015)
In order to determine whether adolescent obesity is a risk factor of low brainpower, a sample of 53 obese adolescents (exposed) and 100 eutrophic adolescents (unexposed) between 12 and 17 years enrolled in state institutions studied district of El Porvenir. Both groups of adolescents were evaluated for nutritional status as measured by body mass index (BMI) and measured brainpower by the Raven's Progressive Matrices Test - Standar. For statistical analysis the Chi square was used by setting the significance level at p<0.05, plus the risk through relative risk with its corresponding confidence interval was calculated. It was found that the frequency of low brainpower was 30.19% in obese adolescents and 21% in eutrophic. There was no association between the variables under study, with no significant difference (p = 0.2066), RR = 0.88 and CI 95% ( 0.72-1.08). We found the prevalence of obesity at 4.14%. Concluding that adolescent obesity is not a risk factor of low brainpower, as measured by the Raven's Progressive Matrices Test- Standar, in students of state educational institutions in the El Porvenir district , Trujillo in 2014